The Impact of Globalization with Thai University Students Enrolled With International Program - Chuanchen Bi & Wei Yang (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Globalization, caused by the rapid development ofInformation and CommunicationTechnology (ICT), is becoming aninevitable trend in the present world.Globalization offers clear opportunities and benefits for the world economies butcomes with substantial social costs that often appear to affect people, especially theyouth. The world’s researchers have paid most of their attention to adolescents, thespecial group of youth whose transition from being children to adulthood, has beenmost affected by the globalization period.Theaim of thisstudy is to study the futureimpacts of globalization towards perspectives in place identity, specifically, thehometown identityofthe youth. As most of the migration workers from Bangkokare coming from northeastern of Thailand, the place where agriculture industry isthe major industry.The young students who enrolled with international program inthe under-graduate levelforms the basis for this research. This study uses primarydata which was collected in Khon Kaen University Internasional College(KKUIC).The research results indicated thatthe respondents from KKUICweremore willing to live in big cities and that traditional music stylesareneitherpopular nor attractive anymore.Among the participating youth students, placeidentity concerning future working place and living place, big cities such asBangkok, Chiang Mai, etc. are more attractive for them. The willing of migration ishigher than 78%.Sustainable development in the agricultural based region needscontributions from the locals.However, the loss of place identity might act againstthis participation.Keywords: Globalization, Future Perspective, PlaceIdentity, YouthStudent, NortheasternThailand